The Lady's Album of Fancy Work for 1850 : Consisting of Novel, Elegant, and Useful Designs in Knitting, Netting, Crochet, Braiding, and Embroidery, with Clear and Explicit Directions for Working the Patterns - Unknown (Salt Lake City, UT : Project Gutenberg, 2004)
"The Lady's Album of Fancy Work for 1850" by Unknown is a collection of instructional designs for various needlework techniques, likely created during the mid-19th century. This versatile volume offers patterns and clear instructions for an array of crafts including knitting, netting, crochet, embroidery, and more. Its purpose is to inspire and facilitate the artistic pursuits of women during that era, emphasizing the blend of creativity and practicality in domestic arts. The opening of this album sets the stage for a rich exploration of needlework, introducing the reader to the art's historical significance and its evolution over time. It details the types of projects included, such as an embroidered front for a lady's cabinet, a crocheted infant's bonnet, and a cover for a cake basket, each with specific materials and detailed instructions outlined. The text suggests a commitment to both aesthetic appeal and technical mastery, providing a valuable resource for traditional handiwork that aims to enrich the domestic sphere and enhance the skills of the diligent needleworker. (This is an automatically generated summary.)
Release date is 2004-06-01
E-text prepared by Julie Barkley, Jayam Subramanian, and Project Gutenberg Distributed Proofreaders
Keywords: Needlework -- Patterns; Fancy work -- Handbooks, manuals, etc